Pattern and impact of hepatic adverse events encountered during immune checkpoint inhibitors – A territory‐wide cohort study - Stephen Lam Chan; Terry Cheuk‐Fung Yip; Vincent Wai‐Sun Wong; Yee‐Kit Tse; Becky Wing‐Yan Yuen; Hester Wing‐Sum Luk; Rashid Nok‐Shun Lui; Henry Lik‐Yuen Chan; Tony Shu‐Kam Mok; Grace Lai‐Hung Wong (Cancer Medicine)
Abstract Background Immune checkpoint inhibitors (ICIs) are increasingly used in the treatment of cancers. We aimed to evaluate the incidence and prognostic impact of hepatic adverse events (AEs) in a territory‐wide cohort of patients who received ICIs. Methods Patients were identified from a territory‐wide database who received ICIs in 2014‐2018. Hepatic AEs were defined as any elevation of liver biochemistries including serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), or total bilirubin levels. Hepatic AEs were graded according to Common Terminology Criteria for Adverse Events (CTCAE) v5.0. Results Total of 1480 patients were identified (mean age 60 years, male 65.5%) and the commonest malignancies being lung cancer (39.6%), liver cancer (16.5%), and gastrointestinal cancer (10.0%). Grade 1‐2 and grade 3‐4 hepatic AEs occurred in 41.3% and 14.9% of patients during ICI treatment, respectively. Patients with liver cancer had the highest rate of hepatic AEs (grade 1‐2:54.1%; grade 3‐4:32.8%). Among 711 patients with hepatic AEs, 383 (53.9%) had raised ALT/AST only, and 328 (46.1%) had concomitant raised ALT/AST and bilirubin levels. In the whole cohort, median overall survival of patients without any hepatic AEs, grade 1‐2 and grade 3‐4 hepatic AEs during ICI treatment was 9.0 months, 7.2 months, and 3.3 months (P < .001), respectively. Similar results on overall survival were obtained among different types of cancers. Conclusions Hepatic AEs occur in more than half of patients receiving ICIs for cancer treatment, with approximately 15% being grade 3‐4 AEs. Occurrence of hepatic AEs is associated with worse prognosis.